Nursing assistance in the organ donation process (Research, Society and Development, 2022)
This article aims to address the experiences and challenges that are encountered by patients and the nursing team when it is necessary to go through an organ donation process. For this, it is necessary to explain what organ transplantation is within the Unified Health System, the SUS, when it can occur and what are the processes that the patient goes through until, in fact, he receives the organ he is capable of. to save your life. Still, it will be available about what is the role of the nursing team in the transplant process, as well as the humanization of the process is able to give medical care a more empathetic look in order to bring the patient and the family closer, since they are, in the minimum, two fragile families, one with the loss of a loved one. The study was carried out through a bibliographic search in the Google Scholar database, in a time lapse of 15 years. Thus, after a thorough reading, the material used as a theoretical basis for the construction of this article was selected. Through the study carried out, it was possible to verify that the nursing team has a very important role in the face of the fragility that the patient goes through until the transplant is performed, and the activity that must be performed by each professional must be very well pre-established, and welcoming the donor family is extremely important for the procedure to be performed.